Risk premia and financial modelling without measure transformation - Eckhard Platen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
This paper describes a financial market modelling framework that exploits the notion of a deflator . The denominations of the deflator measured in units of primary assets form a minimal set of basic financial quantities that completely specify the overall market dynamics, where deflated asset prices appear as martingales. A specific form for the risk premia is obtained as a natural consequence of the approach. Contingent claim prices are computed under the real world measure both in the case of complete and incomplete markets avoiding the use of an equivalent risk neutral measure transformation.
urn:nbn:de:kobv:11-10048184
Keywords: G10; G13; 330; financial market modelling; deflator; risk premium; contingent claim pricing; incomplete market